2018
DOI: 10.1016/j.ejor.2018.01.039
|View full text |Cite
|
Sign up to set email alerts
|

A hybrid condition-based maintenance policy for continuously monitored components with two degradation thresholds

Abstract: Condition-based maintenance (CBM) makes use of the actual condition of the component to decide when to maintain and/or replace the component, thereby maximising the lifetime of the machine, while minimising the number of service interventions. In this paper we combine CBM on one (monitored) component, with periodic preventive maintenance (PM) and corrective maintenance (CM) on the other components of the same machine/system. We implement two thresholds on the degradation level to decide when to service the mon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(31 citation statements)
references
References 21 publications
0
31
0
Order By: Relevance
“…The assumption of perfect information eliminates the effect of measurement noise and allows the CBM more focused on the development of optimal maintenance policy. In literature, numerous CBM models have been proposed assuming perfect inspection (e.g., [10]- [13]).…”
Section: Introductionmentioning
confidence: 99%
“…The assumption of perfect information eliminates the effect of measurement noise and allows the CBM more focused on the development of optimal maintenance policy. In literature, numerous CBM models have been proposed assuming perfect inspection (e.g., [10]- [13]).…”
Section: Introductionmentioning
confidence: 99%
“…Recently, there has been a growing interest in the maintenance modeling of multi-unit systems (Eruguz, Tan, & van Houtum, 2017;Martinod, Bistorin, Castañeda, & Rezg, 2018;Poppe, Boute, & Lambrecht, 2018;Zhang & Zeng, 2015). A review of the CBM policies for systems with multiple components can be found in Keizer, Flapper, and Teunter (2017).…”
Section: Introductionmentioning
confidence: 99%
“…Many research have been done with CBM as a topic, such as [6]- [8], and cost analysis in maintenance such as [9], but there is no research that combine cost analysis of IoT based CBM. CBM system should be taking more advantages with IoT technologies which enabling real time condition monitoring and integrate many data related to CBM in order to take decision when maintenance activity is needed.…”
Section: Introductionmentioning
confidence: 99%